First-Principles Study on the Half-Metallicity of New MXene Materials Nd2NT2 (T = OH, O, S, F, Cl, and Br) - Yang, Kun; Ren, Shuning; Huang, Haishen; Wu, Bo; Shen, Guangxian; Zhou, Tingyan; Liu, Xiaoying (Frontiers in Chemistry, 2022)
This work systematically studied the structure, magnetic and electronic properties of the MXene materials Nd2N and Nd2NT2 (T = OH, O, S, F, Cl, and Br) via first-principles calculations based on density functional theory. Results showed that Nd2NT2 (T = OH, O, S, F, Cl, and Br) have half-metallic characteristics whose half-metallic band gap width is higher than 1.70 eV. Its working function ranges from 1.83 to 6.50 eV. The effects of strain on its magnetic and electronic structures were evaluated. Results showed that the structure of Nd2NT2 (T = OH, O, S, and Br) transitions from a ferromagnetic half-metallic semiconductor to a ferromagnetic metallic and ferromagnetic semiconductor under different strains. By contrast, the structures of Nd2NF2 and Nd2NS2 were observed to transition from a half-metallic semiconductor to a ferromagnetic metallic semiconductor under different strains. Calculations of the electronic properties of different proportions of the surface functional groups of Nd2NTx (T = OH, O, and F; x = 0.5, 1(I, II), and 1.5) revealed that Nd2NO1.5 has the characteristics of semiconductors, whereas Nd2NO(II) possesses the characteristics of half-metallic semiconductors. The other structures were observed to exhibit the characteristics of metallic semiconductors. Prediction of Nd2NT2 (T = OH, O, S, F, Cl, and Br) increases the types of lanthanide MXene materials. They are appropriate candidate materials for preparing spintronic devices.